BIMG-20. METABOLIC BIOMARKERS IN MICRODIALYSATE OF IDH-1 MUTANT TUMORS. (25th March 2021) - Rajani, Karishma; Carlstrom, Lucas; Jacobs, Joshua; Schroeder, Mark; Olson, Ian; Hainy, Matthew; Oh, Juhee; Elmquist, William; Sarkaria, Jann; Burns, Terry
Abstract: Glioblastoma (GBM) is a common deadly malignant brain cancer of the central nervous system, with a median survival of 12–15 months. Scientific advancements are lacking in developing effective therapies for both primary GBM, as well as secondary GBMs, that typically originate as malignant transformation of lower-grade isocitrate dehydrogenase (IDH) 1-mutant tumors. The unique metabolomic profile of IDH1-mutant tumors presents opportunities to develop biomarker signatures of therapeutic efficacy. Microdialysis is an extracellular fluid sampling collection technique utilizing a perfused semipermeable catheter to permit diffusion of molecules between brain interstitium and the perfusate. We hypothesized that microdialysis may identify a metabolomics-based biomarker response to therapy in IDH1-mutant tumors. To test this hypothesis, orthotopic xenografts were generated from patient-derived xenografts (PDX) harboring mutant IDH-1 (R132H). Perfusates were collected from intra-cranial tumors in athymic nude mice sampled at baseline and 72h post treatment with temozolomide (TMZ), an oral alkylating agent used to treat IDH1-mutant gliomas, compared with vehicle treatment. Perfusates were analyzed via untargeted metabolomic profiling using liquid chromatography-mass spectrometry. Tumor specific metabolites such as (D)-2 hydroxyglutarate, were detected in microdialysate from IDH-1 mutant tumor bearing mice compared to non-tumor bearing mice. We also found high levels of metabolites such as 5-methylthioadenosine, and dimethylarginine and wide range of amino acids in microdialysate from IDH-1 mutant tumor bearing mice. TMZ treatment induced changes to metabolites in creatine and histidine metabolism. Our results indicate that microdialysis is a feasible technology to identify metabolomics-based biomarkers in IDH1-mutant gliomas and their response to therapy. We suggest that in vivo intratumoral microdialysis over several days could yield metabolic pharmacodynamic biomarkers of value to therapeutic translation for IDH-mutant gliomas.